DIFFICULTIES IN VERBAL AND NON-VERBAL COMMUNICATION IN AUTISM - Burzawa, Katarzyna Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The ability to establish contact with other people and communicate with them influences the child's further development. Having the ability to communicate verbally and non-verbally plays an important role in life of every person and is decisive in the process of building social relationships with other people. Disorders in the field of communication, speech development and the formation of the language system are one of the main symptoms of autism. In children with autistic disorders speech development is very diverse, even if they can speak, they have huge problems with understanding of the meaning of communication and establishing relationships.The aim of this article is to present the difficulties in verbal and non-verbal communication in autism, which are based on so-called triad of autistic disorders.